Analysis of Indonesian and Malaysian netizens' comments on TikTok social media on urban environmental issues - Brilliana, Arifka; Riyani, Devia; Salma, Parisya; Almeida, Salsha; -, Hendra; Ramlan, Aini Faezah (Faculty of Communication & Media Studies, 2024)
This study analyzes the comments of Indonesian and Malaysian netizens on the social media platform TikTok regarding urban environmental issues. Data was collected from comments on videos discussing urban environmental issues in Indonesia and Malaysia. Data analysis was conducted using qualitative analysis methods. This study aims to compare the behavior of Indonesian and Malaysian netizens in responding to trending environmental issues on TikTok. This study is expected to contribute to understanding how social media, especially TikTok, can be used to raise public awareness about environmental issues and provide insights into the responsibilities of society in terms of cleanliness and behavioral patterns in Indonesia and Malaysia. The results of the study show that the most frequently discussed urban environmental problems by Indonesian and Malaysian netizens are waste and air pollution. Indonesian and Malaysian netizens show concern about urban environmental problems and want concrete solutions from the government and the community. This study provides insights into how Indonesian and Malaysian netizens use TikTok social media to discuss urban environmental issues. These findings can be used to raise public awareness of urban environmental problems and encourage community participation in environmental conservation efforts.